Early immune system alterations in patients with septic shock - Tang, Huiming; Qin, Shuang; Li, Zhanfei; Gao, Wei; Tang, Manli; Dong, Xijie (Frontiers in Immunology, 2023)
This study aims to investigate the early changes in the immune systems of patients with septic shock. A total of 243 patients with septic shock were included in this study. The patients were classified as survivors (n = 101) or nonsurvivors (n = 142). Clinical laboratories perform tests of the immune system’s function. Each indicator was studied alongside healthy controls (n = 20) of the same age and gender as the patients. A comparative analysis of every two groups was conducted. Univariate and multivariate logistic regression analyses were performed to identify mortality risk factors that are independent of one another. In septic shock patients, neutrophil counts, infection biomarkers (C-reactive protein, ferritin, and procalcitonin levels), and cytokines (IL-1β, IL-2R, IL-6, IL-8, IL-10, and TNF-α) increased significantly. Lymphocyte and their subset counts (T, CD4+ T, CD8+ T, B, and natural killer cell counts), lymphocyte subset functions (the proportions of PMA/ionomycin-stimulated IFN-γ positive cells in CD4+ T cells), immunoglobulin levels (IgA, IgG, and IgM), and complement protein levels (C3 and C4) decreased significantly. Compared to survivors, nonsurvivors had higher levels of cytokines (IL-6, IL-8, and IL-10) but lower levels of IgM, complement C3 and C4, and lymphocyte, CD4+, and CD8+ T cell counts. Low IgM or C3 concentrations and low lymphocyte or CD4+ T cell counts were independent risk factors for mortality. These alterations should be considered in the future development of immunotherapies aimed at treating septic shock.